An Overview of Students’ and Teachers’ Factors, and Students’ Perspectives Towards Teachers’ Characters in English Learning - Gunawan Tambunsaribu; Ida Bugus Putu Suamba (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study generally aims at examining any factors that cause the college students still find difficulties in learning English and if there are any bad things experienced by the students from their teachers. The problems in this study are: 1) What are the influences that cause the English students still find English lesson difficult to understand English even though they have learned English for more than 10 years? 2) Did the English students have any bad experiences from their English teachers in the classroom which cause them have difficulties in understanding English lessons? The method used by researchers in this study is a qualitative method with a descriptive approach. The tools used in this study were video recorders and open-ended questions sheets. The primary data in this study is the respondents' answers to some questions delivered to them in the interview session. The respondents are the first-year students of batch 2018 at Gunadarma University located in Bekasi, West Java province. The researcher randomly selected 400 students who were studying English 1 and English 2 subject. It is found that the factors that cause the English learners still find some difficulties in learning English are caused by both internal and external factors. This study also revealed that some students had some bad experiences from their English teachers as long as they have studied English since they started learning English in kindergarten or primary school.